Analisis Kinerja Keuangan di Nilai dari Rasio Likuiditas, Rasio Solvabilitas dan Rasio Profitabilitas pada PT Panambangan di Samarinda - Sri Wahyuni; Rande Samben; Anisa Kusumawardani (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
This research aims to analyze how far the performance on the company when viewed in terms of liquidity, solvency and profitability. The analysis used is the ratio of liquidity, solvency ratio and profitability ratio. The results showed that the company's ability to pay off current liabilities (liquidity) is quite good, seen from the analysis that has been calculated continues to increase. When viewed from the point of solvency, indicating that the company is in a state solvable because the capital owned by the company is able to cover the debts to outsiders. This happens because the amount of assets still have a considerable difference compared to the amount of liability that means the company is able to cover all of its total obligations. When viewed from the point of profitability tend to fluctuate with the increase and decrease percentage indicates that the company is not able to get a good profit. io